Effects of Microstructure Architecture on the Fracture of Fibrous Materials - Theng, Koh Ching; Chung, SM (International Journal of Integrated Engineering, 2020)
Fibrous materials is one of the potential scaffolds used for tissue engineered constructs. One of prerequisite properties for tissue engineered construct is fracture property. The work here study the relationship between microstructure architecture and fracture behaviour of fibrous networks by using finite element analysis. The result shows that fibrous networks are toughened by either reducing the fibre density or cross-link percentage of networks. Such implementation increases the degree of non-affine deformation and produces a more compliant response at the crack-tip region. The non-affine deformation in fibrous networks involves fibre movement like fibre rearrangement and reorientation, where such mechanisms allow stress delocalization to occur at the crack-tip region and results in a better fracture toughness of fibrous networks. The findings form this work provide the design guideline of fibrous materials with enhanced toughness for multiple applications.